Review on Haploid and Double haploid Maize (Zea mays) breeding technology - Takele Mitiku (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Maize (Zea mays L.) is a plant that is grown for human and animal consumption, as well as biofuel and a range of industrial applications throughout the world. By 2020, it is predicted to outnumber wheat and rice in terms of demand. Farmers pick among two types of maize varieties in modern agriculture. Hybrids and open-pollinated varieties are mostly influenced by the current environmental and economic conditions and availability of seed for the preferred variety type. As a result, minimizing the time required for inbred development is critical in supplying varieties that fulfill the needs of modern farmers. The use of doubled haploid technology is the most effective way to accomplish this. The in vivo technique is widely regarded as a valuable tool for improving breeding efficiency. In maize, in vivo haploid induction has been quite successful and several commercial breeding programs currently use it extensively. Many factors such as anther stage, donor plant, and anther preparation were discovered to influence in vitro haploid induction (Androgenesis) in maize. Color indicators are widely used to distinguish typical fertilization kernels from those produced via haploid induction. Because gamete production is hindered in haploid plants, they are sterile. As a result, haploid chromosome duplication is required to permit self-pollination for seed production and genotype preservation. In the production of maize DH lines and colchicine is the most often used chemical as a chromosomal doubling agent. DHs are the ideal material for genetic improvement and genetic studies of maize because of their utility in homozygous line creation, recurrent selection, and induction of mutation, genetic enrichment, and compatibility with other technologies.